Kolonialisme Dan Budaya Populer: Potret Marketing Selebritis Di Hindia Belanda Era 1930-1940 - Pratama, M Al Qautsar (UIN SIber Syekh Nurjati Cirebon, 2025)
The colonial government's propaganda of modern and western culture not only changed lifestyles, but also influenced various aspects from education, social relations, domestic life, to perspectives on identity and gender. This internalization of western values was spread through media such as newspapers, posters, films, advertisements, textbooks, and literary works. The purpose of this study is to identify the transformation and internalization of popular culture in the Dutch East Indies through product marketing strategies through celebrity popularity in the Dutch East Indies and see a comparison of celebrity marketing techniques from the colonial era to the modern era. This research shows that the Bumiputera middle class in Batavia accepted elements of western culture as globalization spread. The colonial government's branding strategy was closely linked to the development of print media at the time, where classified ads frequently appeared and celebrities were utilized to attract public attention. the appearance and lifestyle of celebrities, especially women, reflected social values influenced by colonialism. for example, miss Riboet's name was associated with powder products, and Roekiah became an advertising star after her success in the film Terang Boelan. Although the practice of celebrity marketing has existed since the colonial era, the difference with the present is obvious, especially due to the rapid development of technology and the use of the internet.